Optimized preparation of activated carbon from furfural residue using response surface methodology and its application for bisphenol S adsorption. (24th December 2021) - Liu, Chenglin; Liang, Linlin; Han, Xiuli; Chang, Chun; Chen, Junying; Song, Jiande
Abstract: Furfural residue (FR), a solid waste, was applied as the precursor to prepare activated carbon by steam activation. The Box-Behnken design (BBD) approach-based response surface methodology (RSM) was utilized to optimize the preparation conditions to evaluate their effects on the performance of activated carbon from furfural residue (FRAC). The optimum preparation conditions of FRAC were found as follows: activation temperature of 922 °C, activation time of 62 min, and the mass ratio of char to H2 O of 1:4.5, resulting in 1, 501.84 mg/g of iodine adsorption capacity and 1, 662.41 m 2 /g of specific surface area. The FRAC was characterized and then the adsorption performance of bisphenol S (BPS) on FRAC was investigated. Langmuir and Koble-Corrigan isotherm models were well fitted to the experimental data, and the adsorption kinetics process was perfectly described by the pseudo-second-order model. Thermodynamic parameters showed that the adsorption of BPS was a spontaneous exothermic process. Besides, the regeneration efficiency of FRAC was over 97% after five consecutive cycles. The maximum monolayer adsorption capacity of FRAC for BPS was 3.2848 mmol/g at 298 K, indicating that the FRAC was an excellent adsorbent for the removal of BPS from aqueous solutions. HIGHLIGHTS: Activated carbon derived from solid waste furfural residue (FRAC) by steam activation displayed high surface area up to 1662.41 m 2 /g. Response surface methodology (RSM) based on Box-Behnken Design (BBD) was applied to optimize the preparation conditions of FRAC. The maximum adsorption capacity of FRAC for Bisphenol S (BPS) was 3.2848 mmol/g at 298 K.